2017
DOI: 10.22271/ortho.2017.v3.i4b.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between DHS and PFN in the management of trochanteric and subtrochanteric femoral fractures

Abstract: Introduction:The of aim treatment of these fractures is prevention of malunion and early mobilization. There are various treatment options available, the ideal choice of treatment is internal fixation. Most common used device used for fixation is DHS with side plate assemblies. The best suited implant for management is PFN. PFN is better treatment modality considering its biomechanical properties. The claimed advantage with PFN is that a smaller exposure is required than for a sliding screw it may therefore be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The fluoroscopy time was found to be much more for the PFN is than that for the DHS similar to that reported by Prasad et al 7 The average amount of blood lost in DHS surgery was markedly more than that in PFN surgery comparable to the results reported by Pajarinen et al, Prasad et al and Mundla et al 1,7,8 Similar study by Portakal et al resulted in complete union of the fracture within 4 months which is comparable to 15.11 weeks reported in our study. 9 Functional outcome with PFN was found to be better than DHS for the treatment of intertrochanteric fractures by Pajarinen et al, Nuber et al and also Cruz et al reported that PFN was an efficient means to treat extracapsular proximal femur fractures.…”
Section: Discussionsupporting
confidence: 88%
“…The fluoroscopy time was found to be much more for the PFN is than that for the DHS similar to that reported by Prasad et al 7 The average amount of blood lost in DHS surgery was markedly more than that in PFN surgery comparable to the results reported by Pajarinen et al, Prasad et al and Mundla et al 1,7,8 Similar study by Portakal et al resulted in complete union of the fracture within 4 months which is comparable to 15.11 weeks reported in our study. 9 Functional outcome with PFN was found to be better than DHS for the treatment of intertrochanteric fractures by Pajarinen et al, Nuber et al and also Cruz et al reported that PFN was an efficient means to treat extracapsular proximal femur fractures.…”
Section: Discussionsupporting
confidence: 88%
“…It is also described in cases of targeting errors or progressive impaction of the fracture site. We find 3 cases (case 2, case 3, and case 4) in elderly patients with progressive impaction of the fracture site [ 10 ].…”
Section: Discussionmentioning
confidence: 99%